α11 integrin stimulates myofibroblast differentiation in diabetic cardiomyopathy - Ilana Talior‐Volodarsky; Kim A. Connelly; Pamma D. Arora; Donald Gullberg; Christopher A. McCulloch (2012)
Diabetic cardiomyopathy is characterized by the production of a disorganized fibrotic matrix in the absence of coronary atherosclerosis and hypertension. We examined whether adhesion of cardiac fibroblasts to glycated collagens mediates the differentiation of pro-fibrotic myofibroblasts, which may contribute to cardiac fibrosis. By microarray, we found that methylglyoxal-treated collagen selectively enhanced α11 integrin expression in human cardiac fibroblasts, while levels of other collagen-binding integrins (α1, α2, and α10) were unchanged. Similar increases in α11 integrin mRNA and protein expression were observed in cardiac fibroblasts from streptozotocin (STZ)-treated Sprague–Dawley rats. In human cardiac fibroblasts plated on methyglyoxal-treated collagen and in cardiac fibroblasts from diabetic rats, transforming growth factor (TGF)-β2 but not TGF-β1 or TGF-β3 was increased compared with controls. Knock-down of α11 integrin and TGF-β receptors with small-interfering RNA blocked the increased expression of TGF-β2, α-smooth muscle actin (α-SMA), and α11 integrin that were induced in cells plated on methylglyoxal-treated collagen. Further, inhibition of Smad3 signalling blocked methylglyoxal-collagen up-regulation of α11 integrin and α-SMA expression. Rats with STZ-induced diabetes exhibited increased phosphorylation of Smad3 in cardiac tissues compared with control rats. Interactions between α11 integrins and the Smad-dependent TGF-β2 signalling may contribute to the formation of pro-fibrotic myofibroblasts and the development of a fibrotic interstitium in diabetic cardiomyopathy.